Controlled preparation of undoped Zn2GeO4 microcrystal and the luminescent properties resulted from the inner defects. (June 2021) - Duan, Xiaoxia; Yuan, Man; Ou, Kai; Zhao, Wenxiong; Tian, Tian; Duan, Wubiao; Zhang, Xiqing; Yi, Lixin
Graphical abstract: Highlights: The reaction mechanism of hydrothermal synthesis of Zn2 GeO4 microcrystals was clarified by designing ingenious experiment routes and coordinating with appropriate detection. The morphology and size of Zn2 GeO4 microcrystal are controlled by adjusting the experimental parameters of hydrothermal method and the sintering temperature. The optical properties resulted from the defects and the photoluminescence mechanism of Zn2 GeO4 crystal were studied. Abstract: Zn2 GeO4 microcrystals were prepared by hydrothermal method. Two synthesis routes were tried and the products were studied by analyzing the morphology and the crystalline phases. According to the experimental phenomenon and the XRD spectra of the products obtained at different stages in the preparation process, the possible chemical reactions in the synthesis process were analyzed. Homogeneous dispersion system is needed for preparing well dispersed nanometer or micron Zn2 GeO4 . PH value of the reaction system and the synthesis route affect the particle size and the morphology of the samples deeply. Heat treatment changes the optical properties of the samples and too high temperature leads to the formation of new phase. With the increase of annealing temperature, the emission spectrum first becomes wider and then narrower. This is because the defect kind and the defect intensity vary with sintering temperature. As a result, the CIE Chromaticity coordinates correspond to the emission spectra move from white area to green area. This change is the inevitable result of defect luminescence mechanism.